Optimal Design of the Submerged Entry Nozzle for Thin Slab Continuous Casting Molds - Mingtao Xuan; Min Chen (Metals, 2021)
For the purpose of increasing the capacity of an Angang Strip Production (ASP) continuous caster and the surface quality of a medium-thin slab with mold sections of 150 × (1020–1540) mm2, the present work investigated the influences of the submerged entry nozzle (SEN) structure and main operating parameters on the flow characteristic and temperature distribution in the mold by physical and numerical simulations. The results showed that the typical “double-roll” flow and a central jet were formed through the three-port SEN. With the original SEN, the mean wave height exceeded the critical value of 5.0 mm after the casting speed was increased due to the strong upper recirculation flow. By the slight increment of the bottom port area and the side port angle of SEN, the mean wave height was obviously decreased below 4.4 mm due to the depressing of the upper recirculation flow after the casting speed increased. Meanwhile, the temperature distribution was slightly changed by using the optimized SEN. The practical application showed that the breakout rate decreased from 0.349% to 0.107% and the surface defect rate decreased from 0.54% to 0.19% by using the optimized SEN, while throughput reached the new level of 3.96 t/min.